The effect of financial literacy in the management of BUMDes (The Case study of BUMDes administrators in Nekamese district, Kupang Regency - NTT) - Kefi, Darwin Yopie; Sanga, Marianus Hendrilensio; Seran, Patrisius; Aryuditha, Verylyanny (Jurnal Mantik, 2025)
This study investigates how the management ability of Village-Owned Enterprises (BUMDes) in the Nekamese District correlates with knowledge about finance. This research will examine how the understanding and skills of BUMDes administrators about finance in financial management. It is hoped that the results will provide better insight into how important financial literacy is in improving the performance of BUMDes and provide appropriate policy recommendations to improve financial literacy at the local level. This research will be conducted on BUMDes administrators in 11 villages in Nekamese District, Kupang Regency with a total of 10 respondents. This research is qualitative, and the data analysis tool used in this study is Nvivo (Non-Numerical Unstructured Data Indexing Searching, and Theorizing). NVivo is used to code and analyze data, presenting the results of data analysis in the form of drawings, diagrams, or graphs for thematic, content, comparative, and even analytical purposes, and even to analyze associative, unidirectional, and symmetrical relationships. The results of this study show that BUMDes managers in the Nekamese District have a basic understanding of financial concepts and principles. Respondents showed awareness of the importance of transparency, participation, and financial stability in managing BUMDes. However, there is room for improvement in terms of the implementation of more structured and strategic financial management methods, such as the use of more diversified financial instruments and comprehensive long-term financial planning. Developing the capacity of managers in these aspects can help BUMDes achieve more optimal and sustainable performance